Design of a Geographic Information System for Monitoring the Electrical Distribution Network: A Sustainability Approach - Ibarra Bustamante, Regina; Hernandez Casarrubias, Lorena; Bustamante Salaya, Ivan; Cárdenas de Dios, Juan Pablo; López Leyva, Josué Aarón (My University, 2026)
This paper presents the design of a Geographic Information System for monitoring electrical distribution networks and transitioning to smart grids. The project was developed in Python for an electrical network in Ensenada, Mexico. The system integrates spatial and electrical data into an interactive web platform. The results demonstrate the system's ability to visualize medium- and lowvoltage assets, query attributes, and enhance situational awareness. The discussion highlights that this solution overcomes the limitations of existing fragmented systems and promotes sustainability by improving operational efficiency, enabling the integration of renewable energy sources, and fostering equitable service.
2026 IEEE Conference on Technologies for Sustainability (SusTech)
Keywords: Geographic information systems; Distribution networks; Real-time systems; printing; low voltage; modeling; timing; visualization; monitoring; technology; Campus Ensenada